Pengaruh Reward Dan Punishment Terhadap Kedisiplinan Pegawai - Agus Bandiyono; Kemas Fahmi Hamzah; Nia Ainin Hidaya (Jurnal Ekonomi, 2021)
The era of public information disclosure has made it easier for the public to monitor government performance. As a result, state institutions are increasingly required to make efforts to improve bureaucratic governance, particularly in the management of apparatus resources. One of the efforts made by the government is by giving rewards (awards) or punishment (turning off) to improve the discipline of Civil Servants. This study aims to examine the effect of reward (X1) and punishment (X2) simultaneously or partially as independent variables on the discipline of Civil Servants (Y) as the dependent variable. Testing was conducted on a sample of 30 respondents from a population of 110 people at KPP Madya Palembang. The analysis technique used in this study is multiple linear regression analysis using IBM SPSS Statistics 21 software. The results showed a simultaneous presence of reward and prohibition on employee discipline. Segmentally, the reward has a positive effect on discipline while punishment has no effect on discipline.